Marine capture fisheries in Malaysia with emphasis on overexploited fish stocks - Rahman, Mohammad Mustafizur (2012)
Malaysia is very rich in marine fisheries resource. Marine fisheries sector can make an important contribution to the Malayisian’s wellbeing and prosperity. Marine fisheries sector is of fundamental importance to Malaysia in terms of protein supply, revenue generation and employment. This sector is also important for the food security of Malaysian coastal community. In Malaysia, the total capture production has increased in the last decade. The total capture production in Malaysia has been increasing by 10% since 2000. Although total marine capture production in Malaysia is still increasing every year, the production of some species such as yellowstripe scad and carangids are decreasing very rapidly. Very intensive research is needed for an urgent basis to find out the actual reason of reducing production of these species. However, the possible reason of dramatic reduction in catch might be due to over exploitation. Once any fish stock is overexploited, it produces lower yields than their biological and ecological potential. Therefore, proper management is urgently needed for sustainable production to ensure long-term sustainability in supplying animal protein for Malaysian people. To recover overexploited stock many suggestions has been proposed in the literature. After synthesizing literatures, two main approaches can be proposed for sustainable fisheries production: (i) establishing protected areas, or (ii) limiting capacity and number of fishing vessels, and the allocation of access rights. Continues data collection and their analysis are prerequisite for the successful of both approaches. Therefore, collaboration between scientists, policymaker and fishers is extremely valuable in managing fisheries for sustainable production. Apart from these, managing competing uses such as fishing industry, aquaculture, energy companies, shipping companies, government interests and conservation groups, and reducing by-catch should also be considered for sustainable fisheries production.